Some Evidence for the Remodelling of the Desjatinnaya (Tithe) Church in Kiev - Jolshin, Denis D. (Actual Problems of Theory and History of Art, 2025)
The research is focused on the analysis of the early 19th century drawings and drafts of the small 17th c. chapel built by metropolitan Peter Mohila on the place of the old Desjatinnaya (Tithe) church in Kiev. The issues of the recent archaeological study of the site make the author suggest that the substantial part of the Mohila’s chapel were preserving the walls of the old church. The historical drawings give the clues for the hypothetical remodelling of the southwestern compartment of the ambulatory of the old Tithe church, how it looked after the early 12th c. repairing.